2018
DOI: 10.1002/jcp.27732
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine inhibits melanoma cell migration and metastasis mainly through reducing intracellular levels of β‐catenin and matrix metallopeptidase 9

Abstract: Metastatic melanoma accounts for 60% of death for skin cancer. Although great efforts have been made to treat the disease, effective drugs against metastatic melanoma still lack at the clinical setting. In the current study, we found that lycorine, a small molecule of isoquinoline alkaloid, significantly suppressed melanoma cell migration and invasion in vitro, and decreased the metastasis of melanoma cells to lung tissues in tumor‐bearing mice, resulting in significant prolongation of the survival of the mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…This is consistent with a recent report that Wnt3a expression is associated with MMP9 expression in primary tumor and metastatic site in recurrent or stage IV colorectal cancer (18). Another study also reported the β-catenin regulation of MMP9 in melanoma using a βcatenin inhibitor lycorine (57). However, in the present study, LiCl was ineffective when the tumoroid grew larger, which mimic later stage of tumors.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent report that Wnt3a expression is associated with MMP9 expression in primary tumor and metastatic site in recurrent or stage IV colorectal cancer (18). Another study also reported the β-catenin regulation of MMP9 in melanoma using a βcatenin inhibitor lycorine (57). However, in the present study, LiCl was ineffective when the tumoroid grew larger, which mimic later stage of tumors.…”
Section: Discussionsupporting
confidence: 93%
“…Wu et al ( 21 ) have reported that icariin induces apoptosis in human lung adenocarcinoma cells by activating the mitochondrial apoptotic pathway. Furthermore, lycorine has notable antitumor effects in various types of cancer, such as breast, esophageal, ovarian, prostate, melanoma and liver cancer ( 22 ). Acridone alkaloids are another class of natural products primarily obtained from Swinglea glutinosa , which has selective cytotoxicity against human prostate, lung, breast and liver carcinoma cell lines ( 23 ).…”
Section: Natural Products As Antitumor Drugsmentioning
confidence: 99%
“…The ability of cell invasion was detected via transwell assay as we described before 40 . SPC-A-1 and A549 cells in 200 μl of serum-free DMEM were seeded to the upper chamber, and 500 μl of the complete medium was added to the lower chamber.…”
Section: Cell-invasion Assaymentioning
confidence: 99%
“…Proteins from SPC-A-1 and A549 cells were extracted using the MPER Mammalian Protein Extraction Kit, and the western blotting was performed as previously described 40 . After the proteins were resolved by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) with Tris-glycine running buffer and transferred to nitrocellulose membranes.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation